Electrochemical impedance of porous tantalum solids: modeling of frequency response - Alexander V. Syugaev; Vitaly E. Porsev (Конденсированные среды и межфазные границы, 2024)
The paper proposes a new approach to the analysis of electrochemical impedance spectra of porous tantalum bodies, which involves modeling the frequency response via an equivalent circuit that takes into account the pore hierarchy. It was shown that the proposed circuit describes well the experimental data and allows characterization of the porous structure, including the contribution of different types of pores to the total capacitance of the porous body, characteristic relaxation times, and activation frequencies for different type pores. Two types of samples were analyzed: a porous tantalum body obtained by sintering Ta powder and a porous tantalum body covered with a Ta2O5 dielectric layer. Modeling showed a significant redistribution of contributions from pores of different types into the total capacitance after the formation of Ta2O5 due to the preferential isolation of the smallest pores and/or those difficult to access. The results of modeling of the frequency response of the analyzed samples agree well with the scanning electron microscopy data. The proposed approach has the potential to be advantageous for the technology of tantalum capacitors